Factors enabling and constraining ICT implementation in schools: a multiple case study of three secondary schools in Lesotho - Kalake, Matsitso (Rhodes University, Faculty of Education, Department of Education, 2009)
This study focused on the implementation of ICTs in secondary schools in Lesotho. The main question addressed was: What are the enabling and constraining factors in the implementation of ICTs in schools? The work was undertaken in recognition of the fact that schools in the country were autonomously acquiring computers and using a variety of curricula without much coordination and policies from the government. There were factors encouraging schools to delve into this educational change: and challenges were already evident. This required further investigation. The research approach commenced with a critical review of the literature. Literature was drawn from developed and developing countries in order to understand the process of ICT implementation from a variety of contexts. The enquiry about the implementation process in all the countries focused on the rationale behind the use of ICTs in schools. ICT policies guiding implementation, principal leadership, teacher professional development and ICT resources. The literature review was followed by case studies of three secondary schools in Mafeteng district in Lesotho. Using both qualitative and quantitative methods of research, the study sought to determine from key people in three case study schools their overall understanding of how the process of implementation was carried out and what they perceived as enablers and constraints. The findings revealed that planning, access arrangements, training, support and to a lesser extent resources played a role in either impeding or encouraging the key ICT implementers at school and classroom level. Additionally, the key role of the principal and the MoE were highlighted in the study.
Keywords: Education -- Lesotho; Computer-assisted instruction -- Lesotho; Information technology -- Lesotho; Educational technology -- Lesotho; Education, Secondary -- Lesotho -- Data processing; Education -- Lesotho -- Computer network resources; Educational innovations -- Lesotho; Educational change -- Lesotho